Rancang Bangun Sistem Informasi Pencatatan Transaksi Keuangan Pada Klinik Graha Amani - Sari, Intan Permata; Binawati, Lilis; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Graha Amani Laksana is the company which prioritize public health service for maternity. Day to day, the increasing of population has straight effect with the amount of Graha Amani Clinic patient. The effect for Graha Amani Clinic is they need to have sophisticated system. They need to handle the massive transaction. In the end of the month, they have to make financial reporting. It takes much time to make a simple financial reporting. Based on those problems, Graha Amani Clinic needs a new system which have solve they problem. The system which solve they problem can help the Director to take decision for company. By implementing new system can be the evaluation for company